Analysis of the concepts of Khizra, the forty chiltanas in the epic poem “Manas” - Aitalieva, Tolkun K.; Kulalieva, Kalya O.; Sartbekova, Nurjan K. (Linguistics and Culture Review, 2021)
This study discusses the concepts of Khizra, the forty chiltanas in the epic poem "Manas". The great epic poem of the Kyrgyz people "Manas" contains symbols of many epochs and concepts of Islam that require a separate study. Many words have appeared due to the spread of Islam among the Kyrgyz. In ancient works, there are frequent mentions of words that are incomprehensible to most people such as archaisms and neologisms. In the epic poem, there are episodes where Manas met Khizra, the forty chiltanas, and they told the hero about Islam and told him to follow the path of God. They also help the hero Manas in any difficult situation. This is found in almost all versions of the epic poem "Manas". This study used several research methods including analysis. The concepts of these words were analyzed based on the variants of S. Orozbakov and S. Karalaev. The study also analyses the motives in the epic poem "Manas" in the plot composition of various versions of this legend and the themes revolving around the miraculous birth of the hero and heroic amusements.